2018
DOI: 10.1103/physrevb.97.085154
|View full text |Cite
|
Sign up to set email alerts
|

Spin dynamics and magnetoelectric coupling mechanism of Co4Nb2O9

Abstract: Neutron powder diffraction experiments reveal that Co 4 Nb 2 O 9 forms a noncollinear in-plane magnetic structure with Co 2+ moments lying in the ab plane. The spin-wave excitations of this magnet were measured by using inelastic neutron scattering and soundly simulated by a dynamic model involving nearest-and next-nearestneighbor exchange interactions, in-plane anisotropy, and the Dzyaloshinskii-Moriya interaction. The in-plane magnetic structure of Co 4 Nb 2 O 9 is attributed to the large in-plane anisotropy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 28 publications
6
46
0
Order By: Relevance
“…Here, we study the effects of substitution of Co 2+ by Ni 2+ on magnetic properties of Co 4−x Ni x Nb 2 O 9 by means of neutron diffraction (ND), magnetization and heat capacity measurements, and density functional theory (DFT) calculations. For x = 1, the compound crystallizes in the P3c1 space group with an in-plane weakly noncollinear AFM configuration, in agreement with that recently reported for Co 4 Nb 2 O 9 [12], while the compound with x = 2, similar to Ni 4 Nb 2 O 9 [24], has the crystal structure of the orthorhombic Pbcn space group. A weakly noncollinear ferrimagnetic structure with moments lying along the b axis is revealed for this compound.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Here, we study the effects of substitution of Co 2+ by Ni 2+ on magnetic properties of Co 4−x Ni x Nb 2 O 9 by means of neutron diffraction (ND), magnetization and heat capacity measurements, and density functional theory (DFT) calculations. For x = 1, the compound crystallizes in the P3c1 space group with an in-plane weakly noncollinear AFM configuration, in agreement with that recently reported for Co 4 Nb 2 O 9 [12], while the compound with x = 2, similar to Ni 4 Nb 2 O 9 [24], has the crystal structure of the orthorhombic Pbcn space group. A weakly noncollinear ferrimagnetic structure with moments lying along the b axis is revealed for this compound.…”
Section: Introductionsupporting
confidence: 88%
“…The family of M 4 A 2 O 9 (M = Co, Mn and A = Nb, Tb) compounds was initially reported by Fischer et al [11] to show a similar magnetoelectric coupling under application of a magnetic field below their magnetic ordering temperature. In recent years, several works have been published considering the magnetic, structural, and magnetoelectric features in this series of compounds [9,[12][13][14][15][16][17][18][19][20][21]. Among these compounds, Co 4 Nb 2 O 9 has been reported to show high magnetoelectric coupling at the vicinity of its Néel transition temperature [13,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, measurements of single-crystal neutron diffraction and magnetic susceptibility along different crystallographic directions have shown that the magnetic moments in Co 4 Nb 2 O 9 are confined in the trigonal basal plane instead of parallel to the c axis [12]. Later on, Deng et al showed that the magnetic moments of Co atoms are noncollinearly arranged in the ab plane [23]. A recent neutron-diffraction study on Co 4 Ta 2 O 9 also evidenced noncollinearly canted spin arrangement of Co atoms in the ab plane [24].…”
Section: Discussionmentioning
confidence: 99%
“…Co 4 Nb 2 O 9 is known as one of typical multiferroic quantum spin systems [1], where the magnetic structure is almost collinear in the basal ab-plane below the Néel temperature [2,3]. Under an external magnetic field applied in the ab-plane, it was reported that the electric polarization rotates in the opposite direction at the twice speed relative to the rotation of the magnetic field (2θ-rotation) (see Fig.…”
Section: Introductionmentioning
confidence: 99%